2017
DOI: 10.1021/acsami.7b09914
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-Appended Metal–Organic Frameworks as Highly Active, Selective, and Reusable Catalysts for Mild Aerobic Oxidation of Alcohols

Abstract: Metal−organic frameworks (MOFs) decorated with stable organic radicals are highly promising materials for redox catalysis. Unfortunately however, the synthesis of chemically robust MOFs typically requires harsh solvothermal conditions, which are not compatible with organic radicals. Here, we describe the synthesis of two isoreticular families of stable, mixed component, zirconium MOFs with UiO-66 and UiO-67 structures and controlled amounts of covalently attached TEMPO radicals. The materials were obtained usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 68 publications
(99 reference statements)
2
40
3
1
Order By: Relevance
“…Accordingly, to adopt this catalytic system to heterogeneous catalysts, UiO‐67‐TEMPO with Eu(NO 3 ) 3 was used for aerobic oxidation with a variety of aldehydes with different sizes in the present study (Figure , Tables S1 and S2). To the best of our knowledge, this is the first attempt to utilize a combination system of a metal catalyst and TEMPO species for aerobic oxidation by MOF catalysis, although the previously reported TEMPO only‐functionalized MOFs were successfully demonstrated in the aerobic oxidation of alcohols . The experiments conducted with different catalyst combinations for benzyl alcohol ( 1 a ) oxidation clearly showed that the simultaneous use of UiO‐67‐TEMPO and Eu(NO 3 ) 3 exhibited 97 % conversion to benzaldehyde ( 2 a ), which is the comparable result from homogeneous reaction of Eu(NO 3 ) 3 and TEMPO (entries 3 and 4 in Table S1).…”
Section: Methodsmentioning
confidence: 79%
“…Accordingly, to adopt this catalytic system to heterogeneous catalysts, UiO‐67‐TEMPO with Eu(NO 3 ) 3 was used for aerobic oxidation with a variety of aldehydes with different sizes in the present study (Figure , Tables S1 and S2). To the best of our knowledge, this is the first attempt to utilize a combination system of a metal catalyst and TEMPO species for aerobic oxidation by MOF catalysis, although the previously reported TEMPO only‐functionalized MOFs were successfully demonstrated in the aerobic oxidation of alcohols . The experiments conducted with different catalyst combinations for benzyl alcohol ( 1 a ) oxidation clearly showed that the simultaneous use of UiO‐67‐TEMPO and Eu(NO 3 ) 3 exhibited 97 % conversion to benzaldehyde ( 2 a ), which is the comparable result from homogeneous reaction of Eu(NO 3 ) 3 and TEMPO (entries 3 and 4 in Table S1).…”
Section: Methodsmentioning
confidence: 79%
“…[80] The same oxidation reaction was completed in one third of the time using UiO studied. [81] The aerobic oxidation of benzyl alcohol to benzaldehyde resulted in quantitative yield with UiO-67-TEMPO (38 %) at 25°C in acetonitrile, dioxane, and 1,2-dichloroethane. Interestingly, the use of UiO-67-TEMPO (38 %) as catalyst afforded 48 % yield at 0°C.…”
Section: Other Functionalized Bdc As Catalystsmentioning
confidence: 99%
“…More recently,T EMPO-decorated UiO-66, UiO-67 and UiO-68 MOFs have been synthesized under mild conditions and have been shown to be efficient catalysts fort he selective aerobic oxidation of alcohols. [228,229] In these studies, the authors prepared the TEMPO-substituted MOFs using an ew HClmodulated and low-temperature method to avoid the decompositiono ft he radicals, obtaining highly defective materials with surfacea reas( up to 1310m 2 g À1 )h igher than the parent frameworks. The radical-based catalysts are highly activea nd recyclable for the aerobic oxidation of alcohols under ambient conditions.…”
Section: Magnetically Active Organic Radical Building Blocksmentioning
confidence: 99%